1999
DOI: 10.1016/s0014-5793(99)01447-7
|View full text |Cite
|
Sign up to set email alerts
|

A novel function for a ubiquitous plant enzyme pectin methylesterase: the host‐cell receptor for the tobacco mosaic virus movement protein

Abstract: Plant virus-encoded movement proteins promote viral spread between plant cells via plasmodesmata. The movement is assumed to require a plasmodesmata targeting signal to interact with still unidentified host factors presumably located on plasmodesmata and cell walls. The present work indicates that a ubiquitous cell wall-associated plant enzyme pectin methylesterase of Nicotiana tabacum L. specifically binds to the movement protein encoded by tobacco mosaic virus. We also show that pectin methylesterase is an R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
99
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(99 citation statements)
references
References 24 publications
0
99
0
Order By: Relevance
“…In this regard, it may be significant that calreticulin is not the only ER-associated protein that interacts with TMV MP. Indeed, TMV MP has been shown to interact with PME (Dorokhov et al, 1999;Chen et al, 2000), suggesting that binding to the host cell factors containing signal sequences may represent a general strategy employed by TMV MP to enter the ER secretory pathway; because ER strands span plasmodesmata (Ding et al, 1992b), TMV MP may utilize its association with the ER for transport to plasmodesmata. Obviously, a more active role for calreticulin in viral movement cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this regard, it may be significant that calreticulin is not the only ER-associated protein that interacts with TMV MP. Indeed, TMV MP has been shown to interact with PME (Dorokhov et al, 1999;Chen et al, 2000), suggesting that binding to the host cell factors containing signal sequences may represent a general strategy employed by TMV MP to enter the ER secretory pathway; because ER strands span plasmodesmata (Ding et al, 1992b), TMV MP may utilize its association with the ER for transport to plasmodesmata. Obviously, a more active role for calreticulin in viral movement cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4A shows the interaction between TMV MP and full-length AtCRT1 (lane 1). No interaction was observed between lamin C, known as a nonspecific activator in the two-hybrid system (Bartel et al, 1993), and calreticulin ( Finally, the binding of calreticulin to TMV MP was examined directly using a renatured-blot overlay assay for protein-protein interactions (Dorokhov et al, 1999;Chen et al, 2000). In this approach, calreticulincontaining cell extract is electrophoresed, immobilized on a polyvinylidene difluoride membrane by electroblotting, reacted with purified TMV MP or with an unrelated protein, e.g.…”
Section: Calreticulin-tmv Mp Interaction In Vivo and In Vitromentioning
confidence: 99%
See 1 more Smart Citation
“…PMEs produced by plants take part in important physiological processes, such as microsporogenesis, pollen growth, seed germination, root development, polarity of leaf growth, stem elongation, fruit ripening, and loss of tissue integrity (Tieman and Handa, 1994;Wen et al, 1999;Micheli et al, 2000;Pilling et al, 2000;Micheli, 2001;Pilling et al, 2004). They have also been reported to play a role in response to fungal pathogens (Wietholter et al, 2003) and are required for the systemic spread of Tobacco mosaic virus through the plant (Dorokhov et al, 1999;Chen et al, 2000;Chen and Citovsky, 2003). PMEs are not only produced by plants but also by microbial pathogens (De Lorenzo et al, 1997) and by symbiotic microorganisms during their interactions with plants (Lievens et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…So far, a cell wall-associated pectin methyl esterase (PME; Dorokhov et al, 1999;Tzfira et al, 2000) was shown to specifically interact with TMV-MP30. Also, binding studies of MP30 with cell fractions enriched in plasmodesmal components indicate the presence of potential receptor molecules mediating protein movement via plasmodesmata (Kragler et al, 1998).…”
mentioning
confidence: 99%